2006
DOI: 10.1136/ard.2005.038315
|View full text |Cite
|
Sign up to set email alerts
|

Raised plasma concentration and ex vivo production of inflammatory chemokines in patients with systemic lupus erythematosus

Abstract: Background: Chemokines are involved in leucocyte chemotaxis. Infiltrating leucocytes play an important role of tissue injury in systemic lupus erythematosus (SLE). Objective: To investigate the role of inflammatory chemokines and their association with interleukin 18 (IL18) in SLE pathogenesis and disease activity. Methods: Plasma concentrations and ex vivo peripheral blood mononuclear cell production of inflammatory chemokines IP-10, RANTES, MIG, MCP-1, TARC, IL8, and GROa, and proinflammatory cytokines IL18,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
161
3
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(175 citation statements)
references
References 43 publications
9
161
3
2
Order By: Relevance
“…Therefore, the use of the IP-10 ratio might support an improved diagnosis of active TB disease when combined with the standard diagnostic methods, including microbiology, molecular tests, and clinical and radiological assessments. IP-10 (also known as CXCL10 or IFN-␥-induced protein 10) is a chemokine that is expressed at a high level in inflammatory diseases such as systemic lupus erythematosus, thyroid disease, acute coronary syndrome, and allergies (28)(29)(30). IP-10 is expressed in the bronchial epithelium (31) and in inflamed tissues (32) of active TB patients, who demonstrate upregulation of the helper T (Th) 1-type cytokine IFN-␥.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the use of the IP-10 ratio might support an improved diagnosis of active TB disease when combined with the standard diagnostic methods, including microbiology, molecular tests, and clinical and radiological assessments. IP-10 (also known as CXCL10 or IFN-␥-induced protein 10) is a chemokine that is expressed at a high level in inflammatory diseases such as systemic lupus erythematosus, thyroid disease, acute coronary syndrome, and allergies (28)(29)(30). IP-10 is expressed in the bronchial epithelium (31) and in inflamed tissues (32) of active TB patients, who demonstrate upregulation of the helper T (Th) 1-type cytokine IFN-␥.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, elevated plasma or serum IP-10 levels were found in several studies of small numbers of SLE patients [14][15][16][17][18]; however, the correlation with disease activity was variable. Thus we sought to explore further the serum levels of this chemokine in SLE and their relationship with disease activity and organ manifestations in a larger cohort of 464 oriental lupus patients.…”
Section: Introductionmentioning
confidence: 99%
“…Another study showed that plasma concentrations of IP10 and MCP-1 were increased in SLE patients. They also showed a strong positive correlation between IP-10 levels and SLE disease activity and suggested a possible correlation between SLE renal involvement and IP-10 [113].…”
mentioning
confidence: 87%
“…In SLE, several of these cytokines are overexpressed and contribute to the pathogenesis, in the activity or organ involvement of the disease. Even chemokines (chemoattractan cytokines) that exert their effects by attracting inflammatory cells, including monocytes, neutrophils and T lymphocytes, to sites of inflammation, are implicated in the pathogenesis of SLE, and in some studies, the expression was found to be increased and correlated with renal involvement and disese activity [45,46].…”
mentioning
confidence: 99%